Sosialisasi Padanan Kata Bahasa Indonesia Bidang Komputer dalam Upaya Meningkatkan Kecintaan Terhadap Bahasa Indonesia - Hilaliyah, Hilda (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Indonesian people often use foreign terms in everyday life, one of which is a term in the field of computing. The combination of advances in computer technology and communication technology has given rise to new terms in this field because the terms used are terms in a foreign language. Transferring the terms of the field of science into Indonesian must be done so as not to cause problems. However, in reality, there are still many people who have not received information related to this matter. The solution offered is for the Community Service Implementation Team to provide socialization about the Equivalence of Indonesian Language Computer Terms in Increasing Love for the Indonesian Language at Karang Taruna RT 011 RW 03, Bangka, South Jakarta. The method used in carrying out community service is online. The results achieved are the creation of an understanding of partners related to Indonesian Equivalent Words in the Field of Computers (PAKABAIN BIKOM). In addition, the outputs generated from this activity are in the form of socialization posters and videos.